Pelatihan Pembuatan Video Animasi 3 Dimensi Fotosintesis Mata Pelajaran IPA pada Anak Sekolah Dasar - Rosanensi, Melati; Lanang Sakti; Heroe Santoso; Miftahul Madani; Lela Rahmawati; Suriyati (Insan Kreasi Media, 2024)
Animated video is an audio-visual medium by combining animated images that can move followed by audio corresponds to the animated character. and in this case the service uses 3-dimensional animation. This community service aims to provide knowledge to children to be able to make 3-dimensional animation videos of photosynthesis in natural science subjects so that children can know and learn easily how the photosynthesis process works, using technology. The research method uses the Luther Sutopo method with the following steps: concept, design, material collection, manufacture, testing and distribution. The initial stage that was carried out was to think about the concept, namely the goal, was to produce a 3-dimensional animation video of photosynthesis through the training carried out, and for whom this training was carried out, namely for children who were still attending elementary school. Next, do a 3-dimensional animation design for the video which is made in the form of text, images, audio, video and animation. Then collect the materials needed to make this animated video such as background, images, sound and other supporting materials. After collecting all the materials, this 3-dimensional animated video was made until final editing. Then a test was carried out on the animated video that was made to see whether it was suitable for use as training material for elementary school children. After being declared suitable, it will be immediately distributed to elementary school children. The impact is that it is hoped that children who are still in elementary school will be technologically literate, so that later they can make other animated videos with different material.